A comparison of facial emotion recognition in patients with early- and late-onset temporal lobe epilepsy - Masjedi Arani, Abbas; Batebi, Sepideh; Dolatshahi, Behrooz; Azimian, Mojtaba (Researcher Bulletin of Medical Sciences, 2021)
Background: Epilepsy is accompanied by a series of clinical manifestations of frequent and abnormal discharges of brain neurons. Early onset of epilepsy can normally cause severe cognitive, emotional and social impairments. Therefore, the purpose of the present study is to compare the recognition of facial emotions in patients with early- and late-onset temporal lobe epilepsy. Materials and Methods: In a causal-comparative study, after definitive diagnosis of temporal lobe epilepsy, 80 patients with temporal lobe epilepsy included 40 early- and 40 late-onset are recruited in the study by using purposive convenience sampling. The research instruments were by Ekman test of facial emotion recognition and clinical psychiatric interview based on DSM-V. SPSS 19 analyzed data using multivariate analysis of variance. Results: The results showed significant differences in response accuracy and reaction time of facial emotion recognition between the two groups of early- and late-onset temporal lobe epilepsy (p<0.01). These differences were significant in the response accuracy for recognition of sadness, as well significant differences represented in the reaction time for all six basic emotions (happy, sadness, fear, disgust, anger and surprise). Conclusion: Patients with early-onset temporal lobe epilepsy performed poorly in recognizing sadness. Furthermore, these patients had a longer reaction time in recognizing facial emotions such as; fear, sadness, anger, disgust, happiness and surprise than patients with late-onset temporal lobe epilepsy.